Changes in the users of the social‐ecological system around a reciprocal human‐dolphin relationship - Mauricio Cantor; Bruna Santos‐Silva; Fábio G. Daura‐Jorge; Alexandre M. S. Machado; Débora Peterson; Daiane X. da‐Rosa; Paulo C. Simões‐Lopes; João V. S. Valle‐Pereira; Sofia Zank; Natalia Hanazaki (People and Nature)
Abstract In contrast to many contemporary negative human‐nature relationships, Indigenous Peoples and Local Communities have stewarded nature through cultural practices that include reciprocal contributions for both humans and nature. A rare example is the century‐old artisanal fishery in which net‐casting fishers and wild dolphins benefit by working together, but little is known about the persistence of the social‐ecological system formed around this cultural practice. Here, we frame the human‐dolphin cooperative fishery in southern Brazil as a social‐ecological system based on secondary data from the scientific and grey literature. To investigate the dynamics of this system, we survey the local and traditional ecological knowledge and examine potential changes in its main component—the artisanal fishers—over time and space. Over 16 years, we conducted four interview campaigns with 188 fishers in fishing sites that are more open (accessible) or closed (restricted) to external influence. We investigated their experience, engagement and economic dependence on dolphin‐assisted fishing, as well as the learning processes and transmission of the traditional knowledge required to cooperate with dolphins. Our qualitative data suggest that fishers using accessible and restricted fishing sites have equivalent fishing experience, but those in more restrictive sites tend to be more economically dependent on dolphins, relying on them for fishing year‐round. The traditional knowledge on how to cooperate with dolphins is mostly acquired via social learning, with a tendency for vertical learning to be frequent among fishers using sites more restrictive for outsiders. Experience, economic dependence and reliance on vertical learning seem to decrease recently, especially in the accessible site. Our quantitative analyses, however, suggest that some of these fluctuations were not significant. Our study outlines the key components of this social‐ecological system and identifies changes in the attributes of a main component, the users. These changes, when coupled with changes in other components such as governance and resource units (fish and dolphins), can have implications for the persistence of this cultural practice and the livelihoods of Local Communities. We suggest that continuous monitoring of this system can help to safeguard the reciprocal contributions of this human‐nature relationship in years to come. Read the free Plain Language Summary for this article on the Journal blog.